Deep Learning Classification of High-Resolution Drone Images Using the ArcGIS Pro Software - Amr Abd-Elrahman; Katie Britt; Tao Liu (EDIS)
Deep learning classification of invasive species using widely-used ArcGIS Pro software and increasingly common drone imagery can aid in identification and management of natural areas. A step-by-step implementation, with associated data for users to access, is presented to make this technology more widely accessible to GIS analysts, researchers, and graduate students working with remotely sensed data in the natural resource field.